Boosted by failure? Entrepreneurial internationalisation as a cyclical learning process - Hurmerinta, Leila (Inderscience Publishers, 2025)
How do entrepreneurs learn from failure, and how is this reflected in the internationalisation of their ventures? This study proposes that non-linear internationalisation and experiential learning are tightly intertwined processes in entrepreneurial firms. The reciprocal transfer, analysis and internalisation of experiential knowledge result in a cyclical process wherein internationalisation and learning continuously feed each other. In this process, failures trigger the need to learn and thus fuel the process. This research also highlights the role of the entrepreneur as an important gatekeeper of experiential learning. The entrepreneur’s ability to absorb, digest and transfer the experiential knowledge within an organisation promotes the positive impacts of learning from failure. We further emphasise that entrepreneurs themselves do not have to experience failure; failures experienced by a peer, a firm in the same field or a fellow entrepreneur can be a source for long-term learning.